MAPUCHE AUTONOMY (1907-1992). RENEWS OF AN OLD TRUNK - Ruiz Rodríguez, Carlos (Revista de Historia Social y de las Mentalidades, 2025)
Starting from the historiographical matter, “when  the idea of autonomy appears for  the Mapuche and how it is developed through the tim e?”. We start a search to the presence  of the thought and the action of the autonomist Map uche along the post reduction period.  This will allow us to know how the concept of auton omy started to be used among the  Mapuche people, and also how this idea is becomin g in a strong concept that belongs to  demands of the different segments of the Mapuche p eople in the present.  The Mapuche demands of autonomy came from ancient t imes in the history of this  people and this idea was developing since the decad e of 1970
Keywords: Mapuche people; autonomy; self-determination